Local Politics, Business, People: Issues and Cooperation Strategies - BONDALETOV, Valery Victorovich; MEDVEDEVA, Natalia Vladimirovna; SENCHEVA, Ludmila Victorovna; FROLOVA, Elena Victorovna; Santos, Eugenia (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
This article discusses the functioning of local government in the Russian Federation, explores issues of cooperation between the main subjects of territorial development: local government, businesses and the public. Currently, the factors that determine the effectiveness of local governments are not fully examined. The analysis of the processes of alienation of the people from the local government has a scientific and practical importance. This issue is highly relevant for Russia. The paper focuses on the analysis of the financial resources of local government in the Russian Federation, as well as an imbalance in the budgetary provision of the municipality, and the fact that imbalance creates difficulties in the implementation of some principles of organization of local self-government. The authors emphasize one of the important factors of socio-economic development of the area is to attract investments. The paper summarizes the experience of interaction between authorities and entrepreneurs, reveals the conditions for successful development of social enterprises. The authors build an idea that when traditional management models fail to meet modern requirements of the society, social partnership should become a helpful tool in societal management. This is due to the special consideration of the authors of forms of civil activity of the population at the municipal level, as well as identifying the characteristics of interaction between local authorities and the public. Based on this study the authors draw conclusions about the need to strengthen public control over the activities of local authorities, emphasize the factors that help increase the economic efficiency of municipalities, and accentuate the conditions for acceleration and guidance of the societal management development process.